Identifying best practices for substance-related intimate partner violence screening and referral: a narrative review - Jarnecke, Amber M.; Saraiya, Tanya C. (Frontiers in Psychiatry, 2024)
Introduction: Substance use is strongly associated with intimate partner violence (IPV) and is a modifiable risk factor for IPV. However, lack of comprehensive screening and referral for co-occurring IPV and substance use, along with their psychiatric sequalae, limits the identification and implementation of effective interventions for substance-related IPV. This narrative review (1) investigates the literature on screening and referral practices for IPV, and if these include screening for substance use or other psychiatric comorbidities, (2) provides recommendations for current best practices, and (3) suggests future directions for research and practice aimed at identifying and reducing substance-related IPV. Methods: A narrative literature review examined studies investigating IPV screening and referral programs in clinics. Selected studies were reviewed for: (1) effectiveness, (2) barriers to implementation and sustainability, and (3) responsivity to psychiatric comorbidity, including substance use and substance use disorders (SUD). Results: Findings suggest that effective IPV screening and referral programs have been developed, but disparities in IPV screening exist and many programs only screen for IPV victimization. Barriers to the implementation and sustainability of IPV screening programs include lack of ongoing provider training, funding or institutional support, and direct connection to referral services. Further, many IPV screening programs lack assessment of and referral for comorbid psychiatric conditions, including substance use, and tend not to be routinely implemented in SUD clinics. Discussion: Additional systematic work is needed to develop universal and comprehensive screening and referral programs for substance-related IPV and address issues of long-term sustainability, particularly within SUD treatment settings.